The furniture of the world : essays in ontology and metaphysics - Hurtado, Guillermo.; Nudler, Oscar. (Rodopi Philosophical Studies, 2012)
Seventeen essays make up the body of this anthology. Most of the authors are Latin Americans (although some of them work in other regions), and thus we might say that this volume is, in a very approximate sense, a showcase of recent Latin-American ontology and metaphysics. The remaining authors-Pierre Aubenque, Barry Smith, Lorenzo Peña and James Hamilton-are distinguished teachers who have had important contacts with the Latin-American philosophical community. The articles in this anthology address some of the central questions in ontology and metaphysics: the possibility of a science of being (Aubenque), the different possible approaches to ontology (Hurtado), the recent application of ontology to informatics (Smith), guise theory and its Leibnizian antecedents (Herrera), the reduction of space and time to phenomenological properties (Rodríguez Larreta), the Newtonian ontology of space and time (Benítez and Robles), the relation between truth and the so-called "truth-makers" (Rodríguez Pereyra), the ontological position of the Pyrrhonic skeptic (Junqueira Smith), the limits and difficulties of metaphysical realism (Cabanchik, Pereda), the defense of physicalist or emergentist positions regarding the mental (Pérez), the metaphysical nature of persons (Naishtat), the ontology of cultural entities (Peña), political ontology (Nudler), the relation between ontology and literature (Hamilton), the ontology of art (Tomasini). Some of the works (e.g., those Aubenque and Robles) approach the question from a historical perspective: others examine the most recent philosophical literature on the problems focalized (e.g., those by Pérez and Rodríguez Pereyra), and others offer new approaches (e.g., those of Rodríguez Larreta, Peña or Nudler) to a specific problematic area.